2006
DOI: 10.4049/jimmunol.177.10.7033
|View full text |Cite
|
Sign up to set email alerts
|

Genes within the Idd5 and Idd9/11 Diabetes Susceptibility Loci Affect the Pathogenic Activity of B Cells in Nonobese Diabetic Mice

Abstract: Autoreactive T-cells clearly mediate the pancreatic β cell destruction causing Type 1 diabetes (T1D)2. However, studies in NOD mice indicate that B-cells also contribute to pathogenesis since their ablation by introduction of an Igμnull mutation elicits T1D resistance. T1D susceptibility is restored in NOD.Igμnull mice that are irradiated and reconstituted with syngeneic bone marrow (SBM) plus NOD B-cells, but not SBM alone. Thus, we hypothesized some non-MHC T1D susceptibility (Idd) genes contribute to diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
38
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 53 publications
(72 reference statements)
2
38
0
Order By: Relevance
“…6B). Idd5 and Idd9/11 loci contribute to the T-cell-mediated breakdown of tolerance in NOD B lymphocytes A previous study from our laboratories indicated that introgression of Idd5 or Idd9/11 T1D-resistance loci into the NOD genetic background restored the anergic state of self-reactive B lymphocytes from the IgHEL Â sHEL Dbl-Tg model [9]. We therefore set out to confirm whether these particular Idd loci were involved in the T-cell-mediated breakdown of B-lymphocyte tolerance to the b-cell neo-self-Ag in NOD.insHEL recipients.…”
mentioning
confidence: 78%
See 4 more Smart Citations
“…6B). Idd5 and Idd9/11 loci contribute to the T-cell-mediated breakdown of tolerance in NOD B lymphocytes A previous study from our laboratories indicated that introgression of Idd5 or Idd9/11 T1D-resistance loci into the NOD genetic background restored the anergic state of self-reactive B lymphocytes from the IgHEL Â sHEL Dbl-Tg model [9]. We therefore set out to confirm whether these particular Idd loci were involved in the T-cell-mediated breakdown of B-lymphocyte tolerance to the b-cell neo-self-Ag in NOD.insHEL recipients.…”
mentioning
confidence: 78%
“…NOD.H2 k .insHEL mice were backcrossed to NOD/Lt mice to replace the H2 k congenic region with the H2 g7 haplotype. NOD.IgHEL mice containing B10-derived Idd5 (R444 line) or the NOR-derived Idd9/11 congenic region have also been characterised [9] and were intercrossed to produce a Dbl congenic strain. All experiments were performed on female mice and were approved by the Garvan Institute/St.…”
Section: Micementioning
confidence: 99%
See 3 more Smart Citations